‘‘Atención integral de enfermería en paciente con secuelas por accidente cerebrovascular isquémico’’ - Martinez Cobeña, Evelyn Aylin (2024)
Cerebrovascular diseases are the third leading cause of death and the second leading cause of disability worldwide, primarily affecting middle-aged and elderly adults. The sequelae caused by an ischemic stroke (IS) can have a significant impact on the quality of life of those who experience it. For this reason, the present study aimed to analyze the factors that contribute to the evolution of a patient with sequelae from an ischemic stroke, proposing specialized nursing care to promote recovery. To this end, data collection was carried out, including the medical history and nursing assessment through Marjory Gordon's functional patterns, requiring an interdisciplinary and patient-centered approach, addressing clinical and therapeutic aspects. In this way, altered patterns were identified, such as activity/exercise, self-perception/self-concept, role/relationships, and nutritional/metabolic patterns, which led to proposing care plans based on different needs, resulting in nursing diagnoses such as impaired physical mobility, situational low self-esteem, decreased participation in recreational activities, and risk of impaired skin integrity, with an emphasis on interventions such as emotional support, recreational therapy, and pressure ulcer prevention.